Community Empowerment: Utilization of Corn Waste Into Biochar for Organic-Based Soil Regeneration in Gorontalo - Mayasari Yamin; Supriyo Imran; Ria Indriani; Zulham Sirajuddin (Universitas Muhammadiyah Sidenreng Rappang, 2025)
Biochar application has been evaluated for various types of soil including sand, sandy loam, and clay loam such as soil conditions in Gorontalo Province. This community service aims to provide information related to the benefits of corn cob waste and increase the knowledge and insight of the Ulapato B Village community regarding the manufacture of biochar as a soil conditioner. This community service consists of several activities, namely counseling, direct practice related to the manufacture of biochar, assistance to the community, and monitoring and evaluation. Based on the results of the counseling that has been carried out, it has been able to increase the knowledge and insight of the Ulapato B community regarding the manufacture of biochar using corn cob waste as a raw material. In addition, this activity also increases the community's understanding of the benefits of corn cob waste which they initially only considered as goods that had no ecological information value. Judging from the evaluation stage that was carried out, the responses of the community service participants were positive for each material presented. The material for the stages of making biochar from corn cobs produced the highest percentage, reaching 87.5% and the lowest for the material on Data interpretation related to land area, corn production and the amount of cob waste per year of corn production specifically for data in Gorontalo Province and Indonesia in general, with a percentage of only 15%. This means that community service participants are more interested in direct demonstrations compared to data-based materials.